Mitigating Carbon Emissions in China: The Role of Clean Energy, Technological Innovation, and Political-Institutional Quality - Azam, Anam; Rafiq, Muhammad; Shafique, Muhammad; Yuan, Jiahai (Frontiers in Environmental Science, 2022)
The global warming phenomena arise from the subject of climate change, which draws intellectuals' attention toward replacing polluting energy sources with clean energy sources by continued deployment of innovations. Also, global warming problems put large pressure on governments, individuals, and policymakers. Therefore, for reliable energy supply and economic development, the target of achieving a low-carbon and sustainable environment is needed. In this light, we explore the role of clean energy and technological innovation in carbon emissions reduction in China from 1995-2018. The key outcomes from the fully modified least squares and robust least-squares indicate an elasticity of -0.065 and -0.075, respectively, for the nexus of renewable energy and CO2 emissions. Similarly, nuclear energy, technology innovation and political-institutional quality have a negative influence on CO2 emissions.